Novel functionalized β-nitrostyrenes: Promising candidates for new antibacterial drugs - Anna Boguszewska-Czubara; Karolina Kula; Artur Wnorowski; Anna Biernasiuk; Łukasz Popiołek; Dawid Miodowski; Oleg M. Demchuk; Radomir Jasiński (Elsevier, 2019)
The process of searching for new antibacterial agents is more and more challenging due to the increasing drug resistance which has become a major concern in the field of infection management. Our study presents a synthesis and characterization by IR, UV, 1H NMR and 13C NMR spectra of a homogenous series of 1-EWG functionalized 2-aryl-1-nitroethenes which could prove good candidates for the replacement of traditional antibacterial drugs In vitro screening against a panel of the reference strains of bacteria and fungi and their cytotoxicity towards cultured human HepG2 and HaCaT cells was performed. Antimicrobial results indicated that four of the synthesized compounds exhibited a significant antimicrobial activity against all tested reference bacteria and fungi belonging to yeasts with a specific and strong activity towards B. subtilis ATCC 6633. Two of these compounds had no detectable cytotoxicity towards the cultured human cell lines, making them promising candidates for new antibacterial drugs. Keywords: Conjugated nitroalkenes, Antimicrobial activity, Fungicidal activity, Cytotoxicity, B. subtilis ATCC 6633, HepG2 cells, HaCaT cells